Local people’s attitude and perception towards eco tourism development: empirical evidence from india - Patita Paban Mohanty; Nihar Ranjan Mishra; Sunil Tiwari (Journal of Business on Hospitality and Tourism, 2021)
Ecotourism perceived as a tool for conservation and sustainability across the globe. Ecotourism has become the buzzword and need of this hour focusing community development and conservation. The present study was conducted in five tourism sites in India (western Odisha) to identify the problems and prospects and also to investigate the attitude and perceptions of local people towards eco-tourism development. The study was undertaken through a sociological survey research design having 570 numbers of local people residing within the piloted study area. The research study was dependent on both primary and secondary data from which analysis was done to reach the conclusion. Structured questionnaire and focus group discussion was applied for one to one interview with village people. Quantitative data from the questionnaire was used in the SPPS package for analysis.